STRATEGI RISET PEMASARAN PRODUK UMKM KABUPATEN KUNINGAN JAWA BARAT - Utami, Rahayu Tri; Sudrajat, Deny; Sutrisno, Niantoro; Winarto, Tri; Noorhayati, Taty (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The role of marketing research in marketing plans and strategies is very important through idea generation. Market research can help in creating business ideas. Especially for those who are just starting their own business, this will provide an overview of the market they will be targeting and will be a consideration in taking future steps. Apart from that, the variety of ideas to choose from is not just one business idea, from conducting market research you will get a variety of ideas to choose from. Next, you can note down several variations of existing ideas according to your interests so that they can then become alternative choices. One of the obstacles often encountered in developing a business is difficulty developing a concept. With marketing research, you can obtain a variety of information and data that can be used as an option for creating a business plan. Another thing that is no less important is that through marketing research you will be presented with a variety of the latest trends. This is quite important considering that market conditions move quite quickly from time to time. By following existing trends, you will obtain a variety of information that can be taken into consideration when implementing the next marketing strategy. Marketing research can also play a role in product development. Changing market conditions in terms of tastes and trends must be followed by product development through market research. The role of market research which is no less important is to test the market or market research can be used as an experiment to see whether the results of existing research are in line with the desired expectations so that it will ultimately lead to commercialization or the creation of sales. The things described above have not currently been carried out in a structured manner for MSMEs in Kuningan Regency, so that the products produced have relatively not experienced significant growth either in terms of the number of sales or product variants produced.